The Competence of Out-of-field Teachers and Student Performance: Inputs for an Intervention Plan - Caneda, Christian Jave Robert T.; Biol Jr., Isidro M. (Randwick International of Education and Linguistics Science Journal, 2025)
This study was conducted to determine the extent of demonstration of the teaching competencies of an out-of-field teacher in terms of instructional skills, classroom management skills, guidance skills, and personal and professional skills. It was also part of the scope of this investigation to determine if there is an existing relationship between the extent of teaching competencies as demonstrated by an out-of-field teacher and the level of grade performance of the students. An intervention plan was also proposed as guidelines for the out-of-field teacher based on the findings of the study. The utilized descriptive – correlation research design was utilized the instrument adopted from the study of Villegas (2021) with some modifications of the indicators. The study was conducted among the secondary out-of-field teachers of Southeast Butuan District, particularly a total of 37 out-of-field teachers were the respondents of this research. Findings revealed that Instructional competencies were seen to be often demonstrated by the out-of-field teachers as well as classroom management competencies, guidance competencies and personal and professional competencies equivalent to a performance rating of very satisfactory. On the other hand, 23 students out of 37 earned the grade performance of satisfactory, while 14 or 37.8 belong a fairly satisfactory performance. While the extent of teaching skills as demonstrated by the out-of-field teachers were not seen to have significant relationship to the average grade performance of the students.